Thinking with Ferrar Papers 1422: A c. 1681 Verse Miscellany. (12th June 2020) - Smyth, Adam
Abstract: This article explores a late seventeenth-century manuscript verse miscellany held amongst the Ferrar Papers in Magdalene College, Cambridge, not previously discussed by critics. By attending to both the specific features of this manuscript miscellany (including poems by John Dryden, Katherine Philips. and others), and the larger Ferrar archive, the article considers broader questions about how to read and interpret manuscript miscellanies.